The Implementation Of Scientific Approach In TeachingEnglish At The Eight Grade Of SMP Muhammadiyah 10 Surakarta In 2014/ 2015 Academic Year: A Naturalistic Study - Kartikawati, Yeni; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D. (2015)
This research aims at describing the implementation of scientific approach in teaching English of eight grade at SMP Muhammadiyah 10 Surakarta. The objective of this study is to describe the teaching learning process at SMP Muhammadiyah 10 Surakarta using scientific approach. The writer applies descriptive research especially naturalistic study as a type of this research. The data are derived from event, informant, and document. The methods of collecting data namely: observation, interview, and documentation. The technique of analyzing data are reduction, display, and verification. The result of this research shows in the following elements: (1) The goal of teaching English is to enable in understanding and making a spoken and written form of short functional text and monologue text. (2) The classroom procedure consist of three patterns. The first pattern are Observing, Questioning, Experimenting, Associating, Communicating. The second pattern are Observing, Questioning, Experimenting, Communicating. The third pattern are Observing, Experimenting. (3) The activities during observing cycle, namely question and answer on the observed figure and question and answer on the observed material. The activities during questioning cycle, namley identifying key words and question answer on the observed material. The activities during experimenting cycle, namely brainstorming. The activities during associating cycle is discussion. The activities during communicating cycle namely free writing. (4) The material used are the textbook and powerpoint. (5) The teacher's role are as facilitator, group organizer, and explainer. (6) The student's role are evaluator, active participant, and processor of information. (7) The media used by teacher are picture and LCD. The teachers of SMP Muhammadiyah 10 Surakarta does not always use all the stages of scientific approach in teaching English especially in associating stage.